Assessing the land cover situation in Surkhang, Upper Mustang, Nepal, using an ASTER image - Sharma, Benktesh D; Clevers, Jan; de Graaf, Reitze; Chapagain, Nawa P (Himalayan Journal of Sciences, 2006)
This paper describes the remote sensing technique used to prepare a land cover map of Surkhang, Upper Mustang Nepal. The latest ASTER image (October 2002) and an ASTER DEM were used for the land cover classification. The study was carried out in Surkhang Village Development Committee (area 799 km2) of Upper Mustang region. The study area falls within the Annapurna Conservation Area. Field surveys for training data, ground truthing and spectral signature collection were carried out during May-June 2002. Various image classification algorithms were tested, and the one that yielded the best result was used for image classification. The land cover situations with their aerial extents were identified and topographic analysis was carried out to study the variations of different land covers types in the region. Various species of grasses covered about 36 %; shrubs covered about 32%; bare land, which includes area from completely bare to less than 10% vegetation, constituted about 20% of the land resources of the study area. Grassland was found abundant in east- to south-facing slopes, while shrub species were abundant in flat regions and west- to north-facing slopes. Key words: ASTER image, DEM, land cover mapping, Mustang, Nepal, GIS, remote sensingHimalayan Journal of Sciences 1(2): 93-98, 2003